Entre precariedade e resistência: a cidade como espaço de produção e luta no capitalismo cognitivo - Carolina Salomão Corrêa (Ciências Sociais Unisinos)
This article proposes to identify the relations between the changes in labor and the recent global cycle of struggles. The shared understanding in the investigation is that from the 1970s, capitalism goes through a transformation characterized for the growth of the role of the cognitive dimensions of the work. Unlike the Fordist dynamics, which tended to exclude the worker’s subjectivity in the production processes, the post-Fordist work requires the worker’s subjective participation not only in the production. In other words, the worker participates through their capacity to create, imagine, intervene, but also in the circulation dynamics. Therefore, contemporary production happens, extrapolating the otherwise confined factory spaces, disseminating through the entire social fabric in a cooperation between networks and streets. In that context, the city turns into a space of production and valorization of labor. In face of life and work conditions in the city, increasingly precarious, the city is also a territory for struggles to improve life conditions and the city’s democratic administration. While, in the factories, the workers organized around the rights related to wages and schedules; in the city, the multitude struggles for the physical and incorporeal infrastructure for social life, this that in last analysis feeds the cognitive economy. It is in this direction that the recent revolts in the global metropolises correspond to the struggles of the contemporary work. In this scene, this text proposes to think the necessity to create a new political agenda that makes justice to the new technical composition of work.